2021
DOI: 10.5334/gh.854
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hypertension Up to One Year Postpartum among Women with Hypertensive Disorders in Pregnancy in a Low-Resource Setting: A Prospective Cohort Study

Abstract: Background: Hypertensive disorders in pregnancy (HDPs) are associated with lifelong cardiovascular disease risk. Persistent postpartum hypertension in HDPs could suggest progression to chronic hypertension. This phenomenon has not been well examined in low-and middle-income countries (LIMCs), and most previous follow-ups typically last for maximally six weeks postpartum. We assessed the prevalence of persistent hypertension up to one year in women with HDPs in a low resource setting and determined associated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Three months to 1 year after pregnancy, the prevalence of hypertension among Indian, Cameroonian, Ugandan, Cuban, and Black Dutch women with PE was 15-38%; among Kenyan women with GH/PE prevalence of hypertension was 24% (91,101,102,112,114,120). Prevalence of hypertension was 22% 1 year after pregnancy in Nigerian women with GH, and 61% in women with PE (98).…”
Section: Hypertensionmentioning
confidence: 93%
“…Three months to 1 year after pregnancy, the prevalence of hypertension among Indian, Cameroonian, Ugandan, Cuban, and Black Dutch women with PE was 15-38%; among Kenyan women with GH/PE prevalence of hypertension was 24% (91,101,102,112,114,120). Prevalence of hypertension was 22% 1 year after pregnancy in Nigerian women with GH, and 61% in women with PE (98).…”
Section: Hypertensionmentioning
confidence: 93%
“…Three months to 1 year after pregnancy, the prevalence of hypertension among Indian, Cameroonian, Ugandan, Cuban, and Black Dutch women with PE was 15–38%; among Kenyan women with GH/PE prevalence of hypertension was 24% ( 91 , 101 , 102 , 112 , 114 , 120 ). Prevalence of hypertension was 22% 1 year after pregnancy in Nigerian women with GH, and 61% in women with PE ( 98 ).…”
Section: Cardiovascular Disease Risk Following Hypertensive Disorders...mentioning
confidence: 97%
“…The majority of the studies reported on the risk of hypertension after a pregnancy complicated by HDP ( n = 42; Supplementary Table 6A ) ( 81 83 , 86 , 87 , 89 94 , 97 , 98 , 101 106 , 109 120 , 122 – 124 , 128 , 132 134 , 138 , 139 ). All but one of the comparative studies showed a significantly increased risk of hypertension after pregnancy complicated by HDP, although follow-up time, absolute prevalence/incidence, and risk ratios differed substantially across different studies.…”
Section: Cardiovascular Disease Risk Following Hypertensive Disorders...mentioning
confidence: 99%
“…Hypertensive disorders of pregnancy (HDP), including gestational hypertension (GH), preeclampsia-eclampsia (PE), pregnancy-associated chronic hypertension and chronic hypertension with superimposed preeclampsia ( 1 ), are idiopathic diseases of pregnancy, posing serious threats to the health of mothers and infants. The incidence of PE in developing countries such as China is higher than that in developed countries ( 2 ). Since pregnancy is a special physiological process, hypertension and other diseases with specific occurrences in pregnancy deserve special attention.…”
Section: Introductionmentioning
confidence: 93%